Analisis Beta Saham sebagai Keputusan Investasi pada PT Adaro Energy Indonesia Tbk dan PT Bayan Resources Tbk - Retno Widya Ningrum; Angga Mahardika Putra (LPPM UNIBI, 2023)
In 2022, realized coal production in Indonesia will be 103 percent of the target or 687 million tons from 663 million tons coming from domestic and exports demand.. There are 2 coal industry stocks that are included in the top 10 stocks with the largest capitalization, namely PT Bayan Resources Tbk (BYAN) and PT Adaro Energy Indonesia Tbk (ADRO) with market capitalizations of IDR 700 trillion and IDR 123 trillion. Large market capitalization is usually an attractive thing for investors. Stock investment aims to obtain returns, while returns are in line with risk. One way to measure risk is by calculating the stock's beta value, which aims to see the sensitivity of stock returns to market returns (IHSG) so that investors can find out which stocks are good as investment alternatives. The research method used in this research is a descriptive method with a quantitative approach carried out by beta calculations with Microsoft Excel and analyzing the results and concluding. The conclusion from this research is that ADRO and BYAN's returns have had a positive trend, especially in the last 2 years. However, if you look at the results of ADRO's beta calculations, it tends to move more stably compared to BYAN. The investment decision that investors can take is that it is better to buy ADRO. However, this is also not absolute for investors because each investor has a different risk profile.